2008
DOI: 10.1111/j.1464-5491.2008.02569.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐monitoring of blood glucose changed non‐insulin‐treated Type 2 diabetes patients’ beliefs about diabetes and self‐monitoring in a randomized trial

Abstract: Despite changes in some beliefs about diabetes differing between groups there were no corresponding changes in self-reported health behaviours. This suggests that changes in illness beliefs resulting from SMBG do not cause changes in diabetes-related health behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 25 publications
(42 reference statements)
3
48
0
5
Order By: Relevance
“…This report also states that individuals with diabetes had higher self-care activities. The frequency of diet practice was 5.1 days per week, which is close to the averages of 5.2–6 days per week reported by Kim et al (2004) and 5–5.6 days per week reported by French et al (2008). The blood sugar test was the second most frequently reported self-care activity.…”
Section: Discussionsupporting
confidence: 70%
“…This report also states that individuals with diabetes had higher self-care activities. The frequency of diet practice was 5.1 days per week, which is close to the averages of 5.2–6 days per week reported by Kim et al (2004) and 5–5.6 days per week reported by French et al (2008). The blood sugar test was the second most frequently reported self-care activity.…”
Section: Discussionsupporting
confidence: 70%
“…Evidence suggests that both illness perceptions and treatment beliefs drive patients' self-care behaviours, including medication adherence, and predicts glycaemic control [6]. Furthermore, intervention studies addressing patients' negative diabetes illness and treatment perceptions have demonstrated benefits in self-care behaviours and key health outcomes including glycaemic control [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The self-regulation model describes the perceptions common to people managing an illness and how those with an illness such as T2D make sense of, cope with, adjust to, and manage their condition. Illness and treatment perceptions are linked to self-management behaviors such as adherence to medicines,19,20 lifestyle modification, and self-monitoring 21. The self-regulation model includes emotional (fear, worry, and depression) and cognitive (timeline, severity, identity, cause, and cure/control) representation of illness.…”
Section: Introductionmentioning
confidence: 99%